2019
DOI: 10.1038/s41436-019-0566-2
|View full text |Cite
|
Sign up to set email alerts
|

PEDIA: prioritization of exome data by image analysis

Abstract: PurposePhenotype information is crucial for the interpretation of genomic variants. So far it has only been accessible for bioinformatics workflows after encoding into clinical terms by expert dysmorphologists.MethodsHere, we introduce an approach driven by artificial intelligence that uses portrait photographs for the interpretation of clinical exome data. We measured the value added by computer-assisted image analysis to the diagnostic yield on a cohort consisting of 679 individuals with 105 different monoge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 22 publications
3
43
0
1
Order By: Relevance
“…Studies of more recent versions of DeepGestalt suggested that ethnicity had no major influence on its sensitivity [ 26 , 29 ]. In our set of syndromic images, DeepGestalt’s sensitivity is remarkably high, which is in line with the previous studies highlighting DeepGestalt’s good general sensitivity [ 11 , 36 , 42 ]. This high sensitivity of DeepGestalt was confirmed for both groups of images, those of White persons and those of persons of other ethnicities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies of more recent versions of DeepGestalt suggested that ethnicity had no major influence on its sensitivity [ 26 , 29 ]. In our set of syndromic images, DeepGestalt’s sensitivity is remarkably high, which is in line with the previous studies highlighting DeepGestalt’s good general sensitivity [ 11 , 36 , 42 ]. This high sensitivity of DeepGestalt was confirmed for both groups of images, those of White persons and those of persons of other ethnicities.…”
Section: Discussionsupporting
confidence: 92%
“…No other phenotypic information but 1 portrait photo per case was entered into the system. DeepGestalt's training set was tested not to contain duplicates of images used in this study, as described previously [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…This ingenious approach (called prioritization of exome data by image analysis-PEDIA) was carried out in a large cohort of patients with monogenetic RDs. The authors show that the addition of phenotypic data significantly improved correct disease-causing gene prediction, particularly when deep learning face recognition (with Face2Gene) was encompassed [52].…”
Section: Imaging-based Ddssmentioning
confidence: 99%
“…Studies have shown that facial analysis technologies measured up to the capabilities of expert clinicians in recognizing various developmental and genetic disorders [1][2][3][4]. Clinical dysmorphologists have developed their skill of recognizing a genetic syndrome based on the gestalt, gradually over the years with experience.…”
Section: Next Generation Clinical Practice -It's Man Versusmentioning
confidence: 99%